2013
DOI: 10.18632/oncotarget.1099
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modification and conformational state of Heat Shock Protein 90 differentially affect binding of chemically diverse small molecule inhibitors

Abstract: Heat shock protein 90 (Hsp90) is an essential molecular chaperone in eukaryotes that facilitates the conformational maturation and function of a diverse protein clientele, including aberrant and/or over-expressed proteins that are involved in cancer growth and survival. A role for Hsp90 in supporting the protein homeostasis of cancer cells has buoyed interest in the utility of Hsp90 inhibitors as anti-cancer drugs. Despite the fact that all clinically evaluated Hsp90 inhibitors target an identical nucleotide-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 43 publications
4
62
0
Order By: Relevance
“…Studies also indicate that the sensitivity of a tumor to pharmacologic inhibition may not be driven by the expression of total HSP90 in the tumor cell, but rather by the presence of actively chaperoning HSP90 species [91,98,99]. These species, whose presence are regulated by co-chaperone recruitment and likely also by post-translational modifications, maintain multiple oncogenic pathways dependent on HSP90 activity.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also indicate that the sensitivity of a tumor to pharmacologic inhibition may not be driven by the expression of total HSP90 in the tumor cell, but rather by the presence of actively chaperoning HSP90 species [91,98,99]. These species, whose presence are regulated by co-chaperone recruitment and likely also by post-translational modifications, maintain multiple oncogenic pathways dependent on HSP90 activity.…”
Section: Expert Opinionmentioning
confidence: 99%
“…These species, whose presence are regulated by co-chaperone recruitment and likely also by post-translational modifications, maintain multiple oncogenic pathways dependent on HSP90 activity. In fact, recent proteomic and biochemical studies support the notion that tumor selection in the HSP90 field should be based on more sophisticated functional proteomic insights that measure not only the network of tumor-driving HSP90 clientele but also the abundance and the biochemical nature of the HSP90 fraction available for inhibitor binding [91,98,99]. …”
Section: Expert Opinionmentioning
confidence: 99%
“…It is well-established that increased binding of Hsp90 to its inhibitors is associated with sensitivity of cells to Hsp90 drugs (24,25). We have previously shown that overexpression of the yeast PP5 ortholog (Ppt1) sensitizes cells to the Hsp90 inhibitor geldanamycin (8).…”
Section: Hyper-or Hypoactivity Of Pp5 Mutants Enhances Hsp90 Binding Tomentioning
confidence: 99%
“…These epigenetic modifiers may guide HSP90 to sample multiple distinct conformations that ultimately determine the fate of bound substrate (i.e. proper folding and activation or degradation), and as we are now appreciating, the interaction of a small molecule with HSP90 [8, 56, 57]. …”
Section: Targeting the Stress Chaperome Lessons From Hsp90mentioning
confidence: 99%
“…These inhibitors bind to the ATP binding pocket of HSP90 and prevent HSP90 from cycling between the ADP and ATP bound conformations thus impairing the chaperone activity [41]. Though N-terminal HSP90 inhibitors share a similar binding site their exact mode of binding may be different, and the result is the wide ranging effects on biology [8, 56]. The specific binding mode as well as a discussion on the residues that many of these compounds interact with has recently been analyzed in detail [85].…”
Section: Ligands Targeting the Major Chaperonesmentioning
confidence: 99%